Stevens-Johnson syndrome and toxic epidermal necrolysis: epidemiological and clinical outcomes analysis in public hospitals - Luana Bernardes Arantes; Carmélia Santiago Reis; Alice Garbi Novaes; Marta Rodrigues de Carvalho; Leila Bernarda Donato Göttems; Maria Rita Carvalho Garbi Novaes (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: Adverse drug reactions are harmful and involuntary responses to drugs that occur at doses normally used for a given condition. Among them are Stevens-Johnson syndrome and toxic epidermal necrolysis, both rare and potentially fatal conditions. Objectives: To analyze the epidemiological and clinical characteristics related to patients diagnosed with Stevens-Johnson syndrome and toxic epidermal necrolysis in public hospitals in the Federal District - Brazil. Methods: Retrospective, cross-sectional and descriptive study, in which data were collected referring to patients hospitalized in the public healthcare system of the Federal District from 1999 to 2014. Results: Between 1999 and 2014, 86 cases of hospitalized patients with diagnosis of Stevens-Johnson syndrome and toxic epidermal necrolysis in the Federal District were reported. The majority of patients were women; the most affected age group was 0 to 10 years. Patients older than 60 years (elderly) represent 6.98% of the cases. Most patients admitted to the referral hospital were discharged. However, occurrence of deaths exceeded that of discharge in elderly patients. Limitations of the study: There is fragility in the registry of hospitalization of patients, both in the hospital information system and in the medical records of the reference hospital. Conclusion: There is a need for greater production and better dissemination of information on the incidence of adverse drug reactions.